Web Perizinan Tata Ruang dan Pemanfaatan Lahan Dinas PUPR Kudus - Ikhwan, Muhammad Fahris Noor; Khotimah, Tutik; Putra, Indra Lina (STMIK Banjarbaru, 2026)
Spatial planning and land-use permit services at the Public Works and Spatial Planning Office (Dinas PUPR) of Kudus Regency still encounter obstacles due to manual procedures, including lengthy processing time, limited public access to information, and inefficient archive management. This study aims to develop a web-based spatial planning permit information system that supports permit submission, document management, verification and validation processes, and online monitoring of application status. The research employs a Research and Development method using the Rapid Application Development approach, implemented through requirement analysis, system design, prototype development, black box testing, User Acceptance Testing, and system refinement based on user feedback. System modeling is conducted using Data Flow Diagrams and Entity Relationship Diagrams to ensure alignment between functional requirements, process flows, and database structure. The results indicate that the developed system improves service efficiency, data organization, and transparency of the permitting process, while also enhancing accessibility of information for both the public and administrative staff. The system contributes to the improvement of digital-based public service quality within local government institutions.Keywords: Information system; Spatial planning permit; Land use; Rapid Application Development; Public serviceAbstrakPelayanan perizinan tata ruang dan pemanfaatan lahan di Dinas PUPR Kabupaten Kudus masih mengalami hambatan akibat penggunaan prosedur manual, antara lain keterlambatan proses, keterbatasan akses informasi bagi masyarakat, serta pengelolaan arsip yang kurang efisien. Penelitian ini bertujuan mengembangkan sistem informasi perizinan tata ruang berbasis website yang mampu mendukung pengajuan izin, pengelolaan dokumen persyaratan, proses verifikasi dan validasi, serta pemantauan status permohonan secara daring. Metode yang digunakan adalah Research and Development dengan pendekatan Rapid Application Development, yang dilaksanakan melalui tahapan analisis kebutuhan, perancangan sistem, pengembangan prototipe, pengujian black box dan User Acceptance Test, serta penyempurnaan sistem berdasarkan masukan pengguna. Pemodelan sistem dilakukan menggunakan Data Flow Diagram dan Entity Relationship Diagram untuk memastikan kesesuaian fungsi dan struktur data. Hasil penelitian menunjukkan bahwa sistem yang dikembangkan mampu meningkatkan efisiensi pelayanan, keteraturan pengelolaan data, transparansi proses perizinan, serta kemudahan akses informasi bagi masyarakat dan pegawai, sehingga mendukung peningkatan kualitas layanan publik berbasis digital.Kata kunci: Sistem informasi; Perizinan tata ruang; Pemanfaatan lahan; Rapid Application Development; Pelayanan publik